Implications of Realita Group Counseling for Improving Student Procial Behavior - Kadafi, Asroful; Pratama, Beny Dwi; Suharni, Suharni (Universitas Muhammadiyah Metro, 2020)
This study aims to improve the prosocial behavior of prospective Counselors or Guidance and Counseling Students at PGRI Madiun University (UNIPMA). Prosocial behavior is an important component that must be embedded in the counselor. However, based on the results of preliminary studies, the facts in the field show that the prosocial behavior of UNIPMA students is still relatively low, marked as much as 65% of the total active Guidance and Counseling Study Program Students the level of prosocial behavior is still low. Responding to this problem, there need to be concrete steps to overcome it. One of the strategies that researchers try to offer is to provide reality group counseling to improve student prosocial behavior. This research uses a quantitative approach, with quasi pre-test and post-test design experiments. The results of hypothesis testing found that reality group counseling was declared effective in improving student prosocial behavior. The results of this study have only been tested in a limited sample, so care needs to be taken in generalizing to a wider population.